Answer:
G = 9y²
Step-by-step explanation:
Given
18y³ ← factor out 2y
= 2y(9y²)
2 × 9 = 18 and y × y² = y³
Thus
G = 9y²
Step-by-step explanation: The base of the power in the original equation becomes the base of the log. So we have
.
Next, the exponent in the original equation goes on the other side of the equation and finally, the result in the original equation goes inside the log.
So we have
which is 3² = 9 written in logarithmic form.
This can also be switched around to read
.
So the first choice will be your answer.
My work is also show in the image attached,
I just didn't switch it.
Answer:
c would be the answer you are looking for and please mark brainliest
Step-by-step explanation:
Answer:
Your answer is C.
Step-by-step explanation:
I answered it on paper. When it comes to explaining I have to be person to person. But I hope this helps. :)
Replace x with 2 and solve each equation:
1/2(2) + 4 = 1 + 4 = 5
2+ 6 -1/2(2) -2 = 8-3 = 5
The answer is:
both expressions equal 5 when substituting 2 for x because the expressions are equivalent.